Functional Brain Activation in Response to a Clinical Vestibular Test Correlates with Balance - Noohi, Fatemeh; Kinnaird, Catherine; DeDios, Yiri; Kofman, Igor S.; Wood, Scott; Bloomberg, Jacob; Mulavara, Ajitkumar; Seidler, Rachael (Frontiers in Systems Neuroscience, 2017)
The current study characterizes brain fMRI activation in response to two modes of vestibular stimulation: skull tap and auditory tone burst. The auditory tone burst has been used in previous studies to elicit either a vestibulo-spinal reflex (saccular-mediated colic Vestibular Evoked Myogenic Potentials (cVEMP)), or an ocular muscle response (utricle-mediated ocular VEMP (oVEMP)). Research suggests that the skull tap elicits both saccular and utricle-mediated VEMPs, while being faster and less irritating for subjects than the high decibel tones required to elicit VEMPs. However, it is not clear whether the skull tap and auditory tone burst elicit the same pattern of brain activity. Previous imaging studies have documented activity in the anterior and posterior insula, superior temporal gyrus, inferior parietal lobule, inferior frontal gyrus, and the anterior cingulate cortex in response to different modes of vestibular stimulation. Here we hypothesized that pneumatically powered skull taps would elicit a similar pattern of brain activity as shown in previous studies. Our results provide the first evidence of using pneumatically powered skull taps to elicit vestibular activity inside the MRI scanner. A conjunction analysis revealed that skull taps elicit overlapping activation with auditory tone bursts in the canonical vestibular cortical regions. Further, our postural control assessments revealed that greater amplitude of brain activation in response to vestibular stimulation was associated with better balance control for both techniques. Additionally, we found that skull taps elicit more robust vestibular activity compared to auditory tone bursts, with less reported aversive effects, highlighting the utility of this approach for future clinical and basic science research.